Deindustrialization, structural change and the European productivity dilemma: Growth slowdown and the lost decade - Georg Duernecker (EconPol Forum, 2024)
Aggregate productivity growth in the EU14 has slowed significantly in recent decades. Structural change toward services has contributed significantly to the growth slowdown. Future growth is projected to decline further due to the rise of sectors with stagnant productivity. Europe is projected to fall further behind the US in terms of productivity. R&D tax credits may not cure Europe's productivity malaise due to negative reallocation effects.
Keywords: 330